Fibroblast heterogeneity: Keystone of tissue homeostasis and pathology in inflammation and ageing - Gauthier, Vincent; Kyriazi, Maria; Nefla, Meriam; Pucino, Valentina; Raza, Karim; Buckley, Christopher D.; Alsaleh, Ghada (Frontiers in Immunology, 2023)
Fibroblasts, which are derived from the embryonic mesenchyme, are a diverse array of cells with roles in development, homeostasis, repair, and disease across tissues. In doing so, fibroblasts maintain micro-environmental homeostasis and create tissue niches by producing a complex extracellular matrix (ECM) including various structural proteins. Although long considered phenotypically homogenous and functionally identical, the emergence of novel technologies such as single cell transcriptomics has allowed the identification of different phenotypic and cellular states to be attributed to fibroblasts, highlighting their role in tissue regulation and inflammation. Therefore, fibroblasts are now recognised as central actors in many diseases, increasing the need to discover new therapies targeting those cells. Herein, we review the phenotypic heterogeneity and functionality of these cells and their roles in pathological conditions, and in particular inflammation and ageing.